Biodeterioration of majolica tiles by the fungus Devriesia imbrexigena - Coutinho, M.L. (2020)
This study aimed at evaluating the influence of ageing on the bioreceptivity and biodeterioration of glazed tiles by fungi. These microorganisms have been identified in historical tile colonizing microbial communities. A 12-month laboratory colonization experiment was conducted using pristine and artificially aged tile models inoculated with Devriesia imbrexigena. Fungal growth was evaluated by digital image analysis after incubation. Scanning electron microscopy and micro-Raman spectroscopy were performed to assess tile biodeterioration, revealing that organic acids exuded by D. imbrexigena induced the precipitation of calcium oxalate on the glazed surfaces. Results also showed that the ageing degree was not related to bioreceptivity.